MORPHOLOGICAL AND PHASE EVOLUTION OF COBALT SULFIDE ON CARBON CLOTH VIA CONTROLLED HYDROTHERMAL SYNTHESIS FOR HIGH-PERFORMANCE FLEXIBLE SUPERCAPACITORS - Dinh Hung, Nguyen; Van Cu, Dang; Quang Huy, Le; Thi Thu Thuy, Luong; Van Khu, Le (HNUE Journal of Science: Journal of Natural Sciences, 2025)
Cobalt sulfide nanoparticles were successfully synthesized on carbon cloth (CC) via a one-step hydrothermal method, with varying precursor ratios, hydrothermal temperatures, and hydrothermal times. The crystalline structure, morphology, and composition of the as-prepared CoS were analyzed using X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM, and energy-dispersive X-ray spectroscopy (EDS). Structural analyses confirmed the formation of the hexagonal phase of CoS. Electrochemical measurements revealed that the CoS electrode, prepared with a Co:S ratio of 1:2 at 1600C for 15 h exhibited the highest specific capacitance of 424 F g-1 at a current density of 1 A g-1 and 350 F g-1 at a current density of 5 A g-1. Moreover, the electrode also demonstrated excellent cycling stability, retaining pproximately 90 % of its initial specific capacitance after 1000 charge-discharge cycles at a current density of 2 A g-1. These results highlight a facile, cost-effective, easy-to-implement, and efficient method for utilizing cobalt sulfide-based electrodes for flexible supercapacitor applications.